If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + -1 + -5k = 17 Reorder the terms: -1 + 8k + -5k = 17 Combine like terms: 8k + -5k = 3k -1 + 3k = 17 Solving -1 + 3k = 17 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3k = 17 + 1 Combine like terms: -1 + 1 = 0 0 + 3k = 17 + 1 3k = 17 + 1 Combine like terms: 17 + 1 = 18 3k = 18 Divide each side by '3'. k = 6 Simplifying k = 6
| 1=-3+x/10 | | 7k=8+5k | | 9x-4=3x+14 | | (2-g)=0 | | -9x-4/8=14 | | 14x-3=7x+25 | | 9x+9+7x-5=180 | | (a-1)+1.5a=39 | | 0c-11=21 | | -8x-6/9=-10 | | 6x^2+10=-111 | | -8x-6/-9=-10 | | 50-12x=-22 | | 50-12x=-2 | | 6x+6-8x=6-4(4x+8) | | (4x2+2x-20)/(x+5) | | 2x-x=21 | | 6(n-4)=3h | | -5(-5x+13)=-215 | | y=3/4(3)+3/4 | | 3y-5=11+9y | | 38+7x=8(x-5) | | 3/4(3)+3/4 | | 2x^2-5xy-3y^2-4x+5y+2=2 | | (c-1)+1.5C=39 | | 1/3(x-2/1)=x/4+2/1 | | 9x-5=30+4x | | 4=8(2-k) | | 63x^3-60x^2+12x=0 | | 8x+3/4x+3/4=27 | | 6x+1=3x | | X+2=10/16 |